Prepared cow forage grass with balance nutrition and preparation method thereof - ZHANG ZHIFEI; LUO YU; PAN DIZI; TANG SHOUWEI; WEI ZHONGSHAN (2018)
The invention discloses a prepared cow forage grass with balance nutrition and a preparation method thereof. The invention aims to deliver the forage grass with balance, complete nutrition, make the formula more reasonable, increase the milk yield of cows and improve the disease resistance of cows. The forage grass is prepared from the following components in parts by mass: 30-45 parts of sweet sorghum for feeding, 30-50 parts of feeding corn grass, 20-30 parts of alfalfa, 15-20 parts of witloof, 10-18 parts of perennial ryegrass, 15-20 parts of ramie, 15-30 parts of feeding morus alba L., 4-7parts of purple perilla leaf, 3-6 parts of astragalus mongholicus leaf, 8-10 parts of fruit residue, 2-6 parts of eucommia leaf, 3-5 parts of portulaca oleracea, 3-5 parts of major mineral substanceand 0.6-1.2 parts of trace mineral vitamin. 本申请公开了种营养均衡的配置型奶牛饲草及其制备方法,目的在于，使饲草营养均衡全面，配方搭配合理，能够提高奶牛产奶量以及奶牛自身病患抵抗力，饲草按质量份计，包括：30-45份饲用甜高粱、30-50份饲用玉米草、20-30份紫花苜蓿、15-20份菊苣、10-18份黑麦草、15-20份苎麻、15-30份饲料桑、4-7份紫苏、3-6份黄芪叶、8-10份果渣、2-6份杜仲